Three-dimensional positioning system using Bluetooth low-energy beacons. (October 2016) - Park, Hyunwook; Noh, Jaewon; Cho, Sunghyun
Bluetooth low-energy–based beacons have two different roles: "broadcasting" (by beacon device) and "receiving" (by sensing devices). It allows devices to receive information over a short distance. Thus, many researchers are actively investigating positioning methods that use beacons. However, the distance value of positioning in the existing methods is not always accurate. This article proposes a novel three-dimensional positioning system using Bluetooth low-energy–based beacons. While the conventional methods measure distances by obtaining two-dimensional coordinates( x, y ) through the received signal strength indicator value, the proposed method improves the measurement accuracy by obtaining three-dimensional coordinate values( x, y, z ) . Finally, while comparing the performance of this new method with that of existing methods, the proposed three-dimensional positioning system reduces the positioning error rate by 27.3% compared to the existing two-dimensional triangulation method.